A narrative of the occurrences in the Indian countries of North America, since the connexion of the Right Hon. the Earl of Selkirk with the Hudson's Bay Company, and his attempt to establish a colony on the Red River [electronic resource] : with a detailed account of His Lordship's military expedition to, and subsequent proceedings at Fort William, in Upper Canada. - Wilcocke, Samuel Hull, 1766?-1833.; McGillivray, Simon, 1783-1840.; Ellice, Edward, 1781-1863. (London : Printed by B. McMillan ., printer to His Royal Highness the Prince Regent; sold by T. Egerton .; Nornaville and Fell .; and J. Richardson ., 1817)
Attributed to Samuel Hill Wilcocke--The Macmillan dictionary of Canadian biography / W. Stewart Wallace. Attributed also to Simon McGillivray or to Edward Ellice, the elder--National Union Catalog pre-1956 imprints. Also available in French. See CIHM microfiche no. 42792. Electronic reproduction. Mode of access: Internet. 44